Covid-19 and alcohol associated liver disease. Issue 11 (November 2022) - Deutsch-Link, Sasha; Curtis, Brenda; Singal, Ashwani K.
Abstract: The COVID-19 pandemic is having substantial impacts on the health status of individuals with alcohol use disorder (AUD) and alcohol-associated liver disease (ALD). AUD and ALD have both been impacted throughout the pandemic, with increases in alcohol use during the early stages of the pandemic, reduced access to treatment during the mid-pandemic, and challenges in managing the downstream effects in the post-COVID era. This review will focus on how the COVID-19 pandemic has impacted AUD and ALD epidemiology and access to treatment, and will discuss to address this rising AUD and ALD disease burden.